REAKTUALISASI HADITS MISOGINIS PERSPEKTIF MAQASHID AL-SYARIAH - Sulhadi, Asep; Sholihah, Izzatus (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2024)
Islam as a religion that is rahmatan lil ‘alamin, the teachings contained therein inspire the values of justice, peace, humanity, equality and civility. Thefore, if there is an understanding that is contary with the Islamic values above, so this understanding must be updated and reviewed again. Among the religious text that need to be reviewed is the hadith of prophet SAW which is textually contain the misogynistic element, among them is a hadith which explains about travel prohibition for woman without being accompanied by her mahram. That hadith by some circles serve as argument for curb woman so that not to do activities outside the home. So that, the role of woman in the public realm and social realm become very limited or not at all. The purpose of this research is to reviewed how understand the hadith of prophet SAW about the travel prohibition for woman without being accompanied by her mahram associated with the current context through the Maqashid Syari’ah by looking at the deepest meaning and purpose of the hadith. The method that is a author uses is the descriptive analysis method, by uses approach of Maqashid Syari’ah as a analysis knife to understand the meaning and purpose from the hadith. With uses approach a Maqashid Syari’ah, we can understand that the meaning and purpose from hadith above not to condescending, marginalize, discriminate or restrain the woman. But, it’s all for maintain safety and security at the time. In the current context, means of transportation are more sophisticated and diverse, security conditions are also more secure, so the concept of female mahram in travelling, can be replaced with guarantee of security and safety. Keywords: hadith, Misogynistic, Maqashid Syari’ah